Comparative epigenomics reveals evolution of duplicated genes in potato and tomato. (8th January 2018) - Wang, Lin; Xie, Jiahui; Hu, Jiantuan; Lan, Binyuan; You, Chenjiang; Li, Fenglan; Wang, Zhengjia; Wang, Haifeng
Summary: The evolution of duplicated genes after polyploidization has been the subject of many evolutionary biology studies. Potato ( Solanum tuberosum ) and tomato ( Solanum lycopersicum ) are the first two sequenced genomes of asterids, and share a common polyploidization event. However, the epigenetic role of DNA methylation on the evolution of duplicated genes derived from polyploidization is not fully understood. Here, we explore the role of the DNA methylation in the evolution of duplicated genes in potato and tomato. The overall levels of DNA methylation are different, although patterns of DNA methylation are similar in potato and tomato. Different types of duplicated genes can display different methylation patterns in potato and tomato. In addition, we found that differences in the methylation levels between duplicated genes were associated with gene expression divergence. In particular, for the majority of duplicated gene pairs, one copy is always hyper‐ or hypo‐methylated compared with the other copy across different tomato fruit ripening stages, and these genes are enriched for specific function related to transcription factor (TF) activity. Furthermore, transcription of hundreds of duplicated TFs was shown to be regulated by DNA methylation during fruit ripening stages in tomato, some of which are well‐known fruit ripening TFs. Taken together, our results support the notion that DNA methylation may facilitate divergent evolution of duplicated genes and play roles in important biological processes such as tomato fruit ripening. Significance Statement: It is important to understand the evolution of duplicates after polyploidization. We found that DNA methylation changes between homolog genes were associated with duplicate expression divergence in both potato and tomato, and that many transcription factor duplicates were also regulated by DNA methylation across fruit ripening stages in tomato. We suggest that DNA methylation could facilitate divergent evolution of duplicates, and play roles in important biological processes, such as tomato fruit ripening.